The Implementation Of Authentic Assessment In English Language Teaching - Ayu Sundari; Sabarun (PT. Padang Tekno Corp, 2023)
This study aims to compare four types of authentic assessment in an educational context: project assessment, portfolio assessment, written assessment, and performance assessment. The research method used is library research. The research findings show that authentic assessment is effective in promoting deep concept understanding and application of knowledge in real situations. Project assessment provides students with opportunities to integrate skills and knowledge in tasks relevant to the real world. Portfolio assessment allows students to reflect on their development holistically through a collection of work. Simulation assessments give students the experience of applying knowledge in a structured context. Case study assessments develop critical thinking skills in complex situations. In conclusion, educators need to consider learning objectives and student characteristics in choosing the appropriate type of authentic assessment. This research provides practical guidance for educators in designing effective assessments that motivate students. The results of this study encourage further discussion and research on the development of authentic assessment methods in education.